Implementation of Massive Open Online Course (MOOC) in Pelatihan Jabatan Fungsional Bidan (Pengangkatan Pertama) at Bapelkes Semarang - Resti Dewi; Andreasta Meliala; Dwi Handono Sulistyo (Center for Health Policy and Management, 2023)
In order to improve the quality of health services, competency development is needed, including through training. Bapelkes Semarang has the task and function of organising training, one of which is Pelatihan Jabatan Fungsional Bidan (Pengangkatan Pertama) which uses the Massive Open Online Courses (MOOC) method. The use of MOOC aims to improve the quality and quantity of learning. However, based on the evaluation of the implementation, there are still complaints from participants regarding the implementation of MOOC. So it is necessary to evaluate MOOC. The evaluation results become the basis for the development of cMOOC for training in the health sector including the review of the policies that underpin it. This research was conducted using descriptive qualitative method with in-depth interviews and secondary data collection. The results of the research on training participants showed that not all of them had digital literacy skills so that there were still many training obstacles and to take part in the training they had to use a Letter of Duty so they were not free to attend the training. Facilitators need adaptation in learning the Student Centreed Learning (SCL) model. There is no legal umbrella for the implementation of MOOC. So that if it will be developed into cMOOC, it is necessary to limit cMOOC to knowledge base training or as a pre-requisite programme for other training. As well as the issuance of a legal umbrella that accommodates the principles of MOOC.